First Annual Short Course in Educational Leadership : Littledale Conference Centre, St. John's, Newfoundland, February 22-27,1987. Day 3. Plenary session. Tape 3 of 3. - Memorial University of Newfoundland. School of Continuing Studies and Extension; Memorial University of Newfoundland. Division of Educational Technology (Memorial University of Newfoundland. School of Continuing Studies and Extension; Memorial University of Newfoundland. Division of Educational Technology, 1987)
Question and answer section of the plenary session about the Royal Commission on Employment and Unemployment report. Dr. House comments on the Commission of Inquiry on Unemployment Insurance. The idea of education for earning for life and living a life is addressed. Dr. G.L. Parsons introduces the speakers.